2011
DOI: 10.1166/jnn.2011.3084
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Highly Ordered TiO2 Nanorod Arrays and Their Applications as the Electrode in Dye-Sensitized Solar Cells

Abstract: For the first time, the TiO 2 nanorod arrays have been prepared on ITO substrates at room temperature by dc reactive magnetron sputtering technique. These TiO 2 nanorods have a preferred orientation along the (220) direction and are perpendicular to the ITO substrate. Both the X-ray diffraction and Raman scattering measurements show that the highly ordered TiO 2 nanorod arrays have an anatase crystal structure. The diameter of the nanorod varies from 30 nm to 100 nm and the nanorod length can be varied from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…3(c) illustrates the selected area electron diffraction (SAED) patterns, and the planes at (1 1 1) A UV-vis spectrometer was used to measure the band gap of the sample (Fig. 4) based on the Tauc equation [40],…”
Section: Resultsmentioning
confidence: 99%
“…3(c) illustrates the selected area electron diffraction (SAED) patterns, and the planes at (1 1 1) A UV-vis spectrometer was used to measure the band gap of the sample (Fig. 4) based on the Tauc equation [40],…”
Section: Resultsmentioning
confidence: 99%
“…4). Band gaps of approximately 2.5 eV and 2.9 eV were derived from the Tauc plot 41 for the samples fabricated at 600…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional views show that these films have the nanorod structures. The TEM images shown that the surface of these nanorods is very rough (Meng et al, 2011a), which is favorable for the dye adsorption. From the surface view, it also can be seen that the voids between the grains become big as the sputtering pressure is increased.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the adsorption of the dye molecules, it is necessary to get the porous structure instead of the compact one. In our previous studies, the TiO 2 nanorods have been made by DC reactive magnetron sputtering and the effects of the nanorods dimension, blocking layer, and annealing temperature on the efficiency of DSSCs have been reported (Meng et al, 2010(Meng et al, , 2011a(Meng et al, ,b, 2013Meng and Li, 2011). In this work, the effect of the sputtering pressure on the structure of these nanorods is discussed and the DSSCs were assembled using these TiO 2 nanorods as the electrode.…”
Section: Introductionmentioning
confidence: 87%